2015
DOI: 10.4141/cjas-2015-073
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous sister chromatid exchange in mitotic chromosomes of the chinchilla (Chinchilla lanigera)

Abstract: Kuchta-Gl adysz, M., Wo´jcik, E., Szeleszczuk, O., Niedbal a, P. and Tyblewska, K. 2015. Spontaneous sister chromatid exchange in mitotic chromosomes of the chinchilla (Chinchilla lanigera). Can. J. Anim. Sci. 95: 543Á550. The sister chromatid exchange (SCE) test is a cytogenetic tool with applications as a short-term screen. It is used to assess the influence of physical and chemical factors with potential mutagenic and genotoxic properties on the animal organism. The test results make it possible to eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
(70 reference statements)
1
1
0
Order By: Relevance
“…They observed an increase in the frequency of damage in older individuals compared to young horses. Age is the factor that affects the level of damage generated; the older the animal, the more damage we observe [15,32,44,45]. This dependency was also noted in the present study for each assay used.…”
Section: Plos Onesupporting
confidence: 85%
“…They observed an increase in the frequency of damage in older individuals compared to young horses. Age is the factor that affects the level of damage generated; the older the animal, the more damage we observe [15,32,44,45]. This dependency was also noted in the present study for each assay used.…”
Section: Plos Onesupporting
confidence: 85%
“…According to many researchers, exchanges take place less frequently in the terminal part of chromosomes [32,53]. On the other hand, Kuchta-Gładysz et al [50,54] have reported a very high level of damage in the distal part of the chromosome. Damage in this part of the chromosome is caused by oxidative stress, which results in single-strand DNA breakage in the telomeres.…”
Section: Discussionmentioning
confidence: 99%